A new method for assessing the impact of medial temporal lobe amnesia on the characteristics of generated autobiographical events. (May 2016) - Lenton-Brym, Ariella; Kurczek, Jake; Rosenbaum, R. Shayna; Sheldon, Signy
Abstract: Constructing autobiographical events involves an initial phase of event selection, in which a memory or imagined future event is initially brought to mind, followed by a phase of elaboration, in which an individual accesses detailed knowledge specific to the event. While considerable research demonstrates the importance of the medial temporal lobes (MTL) in the later phase, its role in initial event selection is unknown. The present study is the first to investigate the role of the MTL in event selection by assessing whether individuals with MTL lesions select qualitatively different events for remembering and imagining than matched control participants. To do so, we created "event captions" that reflected the type of events selected for an autobiographical event narrative task by four individuals with MTL amnesia and control counterparts. Over 450 online raters assessed these event captions on qualitative dimensions known to vary with autobiographical recall (frequency, significance, emotionality, imageability, and uniqueness). Our critical finding was that individuals with MTL amnesia were more prone to select events that were rated as more frequently occurring than healthy control participants. We interpret this finding as evidence that people with impaired episodic memory from MTL damage compensate for their compromised ability to recall detailed information by relying more heavily on semantic memory processes to select generalized events. We discuss the implications for theoretical models of memory and methodological approaches to studying autobiographical memory. Highlights: Medial temporal lobe (MTL) damage impairs detailed event memory. We use a novel method to assess if MTL damage affects the events chosen for recall. We assessed the characteristics of events selected by patients with MTL amnesia and controls. MTL damage led to a reliance on selecting frequent/generic events for recall. This result is interpreted as a form of event selection compensation for impaired memory.